Object Query Computing Optimization in the Dynamic Information Model DIM - V. S. Roublev (Моделирование и анализ информационных систем)
The problem of algorithm for organization of the object queries execution [1] for a new object DBMS technology DIM [2] is considered such that the computational complexity of the queries execution is as little as possible. Solutions of this problem may be taken as a basis for the development of a query compiler.